The relationship of psycho-autonomic status of pregnant women suffering from vegetative dystonia, with pregnancy, birth and status of newborn - K P Masliankina; L S Alexandrov; A I Ishchenko; N V Tutter; A P Niconov (IP Berlin A.V., 2014)
Тhe article discusses the relationship of psycho-autonomic status of pregnant women suffering from vegetative dystonia, with pregnancy, childbirth and the newborn state. It is shown that pregnant women with autonomic dysfunction are the features of obstetric-gynecological history, state of the vegetative nervous system and mental state.